MENGEMBANGKAN UMKM KUE ADREM G&G MBAK ASIH - Putranti, Latifah; Aryandha, Pradita Nindya; Herdiany, Hapsari Dyah; Hasbi, Syahrul (Jurnal Industri Kreatif dan Kewirausahaan, 2023)
This community service is an activity to revive MSMEs that have been affected by the Covid-19 pandemic. One way to increase sales figures again is to improve product packaging and digital marketing to make it more attractive and informative. In addition, product packaging and digital marketing are tools for promotion. Promotion is an attempt to inform a product with the aim of attracting potential consumers to buy or consume it so that sales are expected to increase. Adrem Cake GG Mbak Asih is an MSME engaged in the culinary field of Bantul, DIY. Community service is carried out in two stages. The first stage is education about the importance of packaging and digital marketing to support sales and promotions. The second stage is to provide training on packaging selection, practice of packaging products, explaining websites and placing business locations on Google Maps. After that, mentoring is carried out so that it can be implemented optimally.